Normas internacionais de contabilidade: percepções dos peritos criminais federais sobre os impactos de sua adoção na atividade de perícia oficial realizada em fraudes contábeis no Brasil - Souza, Audrey Jones (2012)
The impacts of adopting International Accounting Standards (IFRSs) has been the subject of debate in the professional and academics media, however, little has been researched on the impact of adopting IFRSs in federal forensic expert. Therefore, the objective of this study is to capture and analyze the perception of the federal forensic expert on the impacts of the adoption of IFRSs in the investigative official activity held in accounting fraud. It was based on a quantitative and qualitative approach used to assess associations between perceptions, resorting to the chi-square test and content analysis, respectively. The results showed that most respondents agree partially or fully that the adoption of IFRS will facilitate the work of federal forensic expert, finding statistical association with the perception that fraud without financial engineering is easier to prove and with the perception that more space for technical judgments have positive impact on the activity of federal forensic expert. Other benefits mentioned were the increased comparability, reduction of complexity and professional development. However, it was verified the possibility of increased risks in the technical objections to expert reports, the risk of bias and the need for qualification, but without statistical association with the perception that IFRSs or otherwise facilitate the examination. No statistical differences were identified on the basis of perceived levels of knowledge of the precepts on IFRSs and the theoretical and practical knowledge of respondents. The study has limitations concerned primarily to generalization of the results, since the intended approach was qualitative and quantitative, and the number of answered questionnaires did not allow performing statistical tests with greater robustness.